(untitled) (American International Journal of Business and Management Studies, 2020)
This Paper examined the role of HRM factors in achieving Quality of work life in the organization. The main objective of this paper therefore was to determine any significant relationship that main exist between HRM factors such as Engagement , Talent Management , Compensation, learning and development on the one hand and quality of work life on the other. The study adopted cross sectional design and employ survey as the research strategy to elicit responses from respondents in UBA PLC. The study employed the use of questionnaire as the main research instrument. It was revealed from the hypotheses tested that HRM factors are significantly related to work life balance, and therefore HRM factors are major determinants of quality of work life in the organization.